RESPON PERTUMBUHAN DAN FISIOLOGIS TANAMAN SAWI (Brassica rapa var. Parachinensis) YANG DIPAPAR TIMBAL (Pb) - Vanny Harianto; Selvia Dewi Pohan (JBIO: jurnal biosains (the journal of biosciences), 2018)
The purpose of the study is to determine the influence of lead (Pb) on the growth and physiology of mustard (Brassica rapa var. Parachinensis). The research was carried out in greenhouse and chemistry laboratory of Universitas Negeri Medan and Laboratorium Kesehatan Medan from April to August 2018. This research was using a Completely Randomize Design (RAL) with 4 treatments and six replications. The treatment is the solution lead (Pb) with 4 levels of dose : 0 ppm , 1 ppm, 3 ppm, and 5 ppm. Data was analyzed by analysis of variance (ANOVA) on the SPSS program. The results showed that the lead affect the growth and physiology of mustard. Mustard which were given lead 1,3, and 5 ppm have lower height (49 cm; 41,4 cm; and 29,8 cm) than control (82,5 cm). The higher concentration of lead solution caused the lower plant height. This effects as same as to the number of leafs, plants that were treated with lead have fewer leaves (31,3 sheets; 28 sheets; and 23 sheets) than controls (38,6 sheets). The lead also affects the weight of mustard plants. Mustard that treated with lead has a lighter weight than the control. Plants treated with lead 1,3, and 5 ppm have lower chlorophyll levels (7,20 mg/L; 5,08 mg/L; and 2,17 mg/L) than controls (11,76 mg/L).